Youths' sustainable livelihood with information and communication technologies: toward an ICT for development quality model - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Omar, Siti Zobidah; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril (Science Publications, 2014)
Creating and developing sustainable livelihood opportunities for young people is reliant, in part, on an understanding of the social and economic process and context that affect their lives. The goals of creating youths' sustainable livelihood is to establish appropriate ways to improve the assets on which young people may draw to meet their current and long-term needs and to decrease the challenges they face. Nowadays, the centrality of youth as a target group for ICTs is highlighted. Research findings in the past decade have shown that ICTs are an effective means of broadening livelihood opportunities.Thus, this study examines the conceptual debate about the development of resource strategies, including ICTs, for young people to mobilize their livelihood assets for community development and information-sharing purposes and also to overcome the barriers to using ICTs by suggesting a model and prescriptive guidelines. Going forward, this study provides an account of the cumulative knowledge of how ICTs are used by young people as an integral part of their everyday lives and emphasizes the importance of selected factors, including affordability, relevance, trust and support for the community of practice for the youth community, in utilizing ICTs to expand education, enhance health care, improve assets and develop mechanisms for community support.